Product Variety and Price on Purchase Decisions at a Retail Grocery Store in Indonesia - Aldi Mahendra; Yateno Yateno; Jati Imantoro (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study examines the partial and simultaneous effects of product variety and price on consumer purchase decisions at Toko Firantika, a rural grocery store in Mesuji District, Lampung Province, Indonesia, amid growing competition from modern retail and online commerce. Methodology: This study employed a quantitative survey. Data were collected from 97 consumers selected through accidental non-probability sampling method. The sample size was determined using Cochran’s formula at a 95% confidence level and a 10% margin of error. Data were gathered using a structured Likert-scale questionnaire (1–5) and analyzed through multiple linear regression with classical assumption tests using IBM SPSS Statistics version 25. Results: Product variety positively and significantly influenced purchase decisions (β= 0.242; t= 2.499; p= 0.014). Price also positively and significantly affected purchase decisions (β= 0.349; t= 4.324; p= 0.000) and was the dominant predictor. Simultaneously, both variables significantly influenced purchase decisions (F= 13.675; p= 0.000), explaining 22.5% of the variance (R²= 0.225). Product size variety and price affordability were the strongest indicators of their respective constructs. Conclusions: Product variety and price are significant and complementary determinants of consumer purchase decisions in rural grocery retailing. Limitations: The model explains only 22.5% of the purchase decision variance, indicating the influence of other factors. Contribution: This study provides empirical evidence on the determinants of purchase decisions in rural MSME grocery retail and practical insights for enhancing competitiveness through product assortment and pricing strategies.